Enabling nanoscale flexoelectricity at extreme temperature by tuning cation diffusion - Leopoldo Molina-Luna (Nature Portfolio, 2018)
The limited number of materials with a switchable electrical polarization available for applications can be increased by exploiting the flexoelectric effect. Here, switchable polarization in nanoparticles induced by an elemental distribution dependent strain gradient up to 800 °C is demonstrated.